Effects of Zero Velocity Update on Total Displacement for Indoor Inertial Positioning Systems - ULAMIS, Faruk; LUY, Murat; CAM, Ertugrul; UZUN, Ibrahim (International Journal of Intelligent Systems and Applications in Engineering, 2017)
In this paper; the effects of Zero Velocity Update method, which is one of the most important components of indoor inertial positioning systems, on total displacement is studied. For this purpose, acceleration and angular velocity measurements on three axes are obtained by a low cost foot mounted inertial measurement unit while walking. The obtained acceleration values are processed and velocity and total displacement are estimated by using double integration. Velocity and displacement estimations done at the end of the each step have been calculated with and without ZUPT algorithm and the results have been compared. Furthermore, in order to understand ZUPT algorithm well, a rectangular shape is plotted with the system containing IMU and microprocessor by stopping at every corner. ZUPT algorithm is implemented at each stop on the corners of the rectangular shape. The results are plotted in MATLAB. Effects of the errors on total displacement are pointed out.